(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
The purpose of this paper is to investigate to what extent the academic and professional training received at the university is a contributing factor to the labor insertion and subsequent professional development of graduates. In this understanding, and to shed light on this problem situation, we analyze two linked issues: a) the relationship between the university and the labor market, and b) the monitoring of university graduates. Regarding the first, we conclude that university graduates should be trained with the professional skills and abilities not only to respond to short-term labor market needs, but also to anticipate and adapt themselves, with the necessary flexibility, to contextual changes. Regarding the follow-up of graduates, we conclude that the university should do it in a systematic and continuous way to favor their insertion and professional development, since this has become a strategic aspect in the definition of educational policies and accreditation processes and evaluation.